Pregnancy Outcome in Kidney Transplant Patients - Yassaee, Fakhrolmolouk; Moshiri, Farnaz (Urology Journal, 2009)
<!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE AR-SA MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--> <!-- /* Font Definitions */ @font-face {font-family:"Cambria Math"; panose-1:2 4 5 3 5 4 6 3 2 4; mso-font-charset:0; mso-generic-font-family:roman; mso-font-pitch:variable; mso-font-signature:-1610611985 1107304683 0 0 159 0;} @font-face {font-family:Tahoma; panose-1:2 11 6 4 3 5 4 4 2 4; mso-font-charset:0; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:1627400839 -2147483648 8 0 66047 0;} /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-unhide:no; mso-style-qformat:yes; mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman","serif"; mso-fareast-font-family:"Times New Roman";} p.CharCharCharChar, li.CharCharCharChar, div.CharCharCharChar {mso-style-name:" Char Char Char Char"; mso-style-unhide:no; margin-top:0cm; margin-right:0cm; margin-bottom:8.0pt; margin-left:0cm; line-height:12.0pt; mso-line-height-rule:exactly; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Tahoma","sans-serif"; mso-fareast-font-family:"Times New Roman"; mso-bidi-font-family:"Times New Roman";} .MsoChpDefault {mso-style-type:export-only; mso-default-props:yes; font-size:10.0pt; mso-ansi-font-size:10.0pt; mso-bidi-font-size:10.0pt;} @page Section1 {size:612.0pt 792.0pt; margin:72.0pt 72.0pt 72.0pt 72.0pt; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0;} div.Section1 {page:Section1;} --> <!--[if gte mso 10]> <![endif]--> Introduction: Advances in surgical techniques and immunosuppressive therapy have improved the survival and quality of life in organ transplant patients. Thus, the number of organ transplant women at their reproductive age has also increased. We sought to investigate the allograft and obstetric outcomes in pregnant kidney recipients. Materials and Methods: Seventy-four kidney recipient women with 95 conceptions during their posttransplant period were evaluated. Pregnancy outcome, kidney allograft function, and maternal, fetal, and neonatal complications were evaluated in these patients. Results: The mean interval between kidney transplantation and pregnancy was 41.0 ± 9.5 months. Twenty-three pregnancies (24.2%) were unsuccessful due to abortion and stillbirth. The mean birth weight was 2385.0 ± 161.7 g and 45 newborns (62.5%) had a birth weight less than 2500 g (low birth weight). The mean Apgar score of the live babies was 7.9 ± 0.7. Forty-four (61.1%) babies were admitted to neonatal intensive care unit and early neonatal death happened in 4 (5.5%). Fifteen mothers (15.78%) had an uneventful perinatal period. The most common maternal complications in the 95 pregnancies were anemia in 62 (65.3%) and preeclampsia in 45 (47.4%). Three patients 3 (3.2%) lost their graft and 6 (6.3%) had impaired kidney allograft function 2 years after pregnancy. Conclusion: Pregnant kidney allograft recipients should be considered as high-risk patients needing special care under the supervision of a team of obstetricians and nephrologists.